The language of house-museums from private to public: a case-study of Leighton House - Ozer, Hatice Sule (2025)
This study examines the transformation of private houses into public museums, focusing primarily on properties originally built as artist studio houses. It explores the relationship between these artist studio houses and their new roles as museums, particularly emphasising the intimate and personalised aspects of these spaces. The research aims to understand how these places maintain their private narratives while also functioning as public cultural institutions. The study focuses on three primary inquiries: the unique characteristics of artist studio House-Museums, the methods adopted by museum curators and/or directors for interpreting and managing their spaces, and the changing roles and perspectives of visitors during their public museum visits. Employing a grounded theory approach within an interpretivist framework, this research uses a mixed-methods strategy to investigate the complex, multi-layered nature of the case study of artist Frederic Leighton’s studio house in Holland Park, London, and the full spectrum of visitor experiences. This approach allows theories to emerge from the data collected during the case visits, thereby accommodating the intricate and often subjective experiences of museum visitors. The results are presented within a new analytical framework: The 3T Conception which explains the evolution of these once-private residences into public museums through the processes of Transformation, Transposition, and Transgression. Transformation refers to the physical conversion of private houses into public spaces. Transposition involves recontextualising the artist’s personal artifacts, daily furniture, and private spaces for public viewing and needs. Transgression refers to the visitor experience of crossing both physical and experiential boundaries, significantly altering the nature and perception of the House-Museum. The findings of the research enhance the understanding of the complex dynamics associated with the transition of private residences into public cultural institutions. It suggests that the interpretation and display strategies used by semi-private artist studio houses may struggle to adequately integrate both realms of private space and public display, adding to the questioning of ambiguous, confusing, or conventional notions of museum spaces. Additionally, it suggests a reassessment of visitor involvement in these distinctive environments; House-Museums.